Nicardipine inhibits N-type calcium channels in dbcAMP-differentiated neuroblastoma x glioma hybrid cells (NG 108-15 cells). - Li Sheng-nan; Brater Manfred; Andreas Klaus (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the possibility of dihydropyridine inhibition of N-type calcium channels. METHODS: Effects of nifedipine and nicardipine on the high K(+)-induced intracellular Ca2+ concentration ([Ca2+]i) increase were studied by measuring [Ca2+]i using the fluorescent indicator Fura-2. RESULTS: Pretreatment of cells with nifedipine 50 mumol.L-1 inhibited the high K(+)-induced [Ca2+]i transient by about 60% (n = 3); however, pretreatment of cells with nicardipine 10 mumol.L-1 completely prevented the high K(+)-evoked [Ca2+]i increase in dibutyryl cyclic AMP (dbcAMP)-differentiated NG 108-15 cells (n = 5). The high K(+)-induced [Ca2+]i increase was mediated by L- and N-type voltage-sensitive calcium channels (VSCC) in NG 108-15 cells. CONCLUSION: Nicardipine at micromolar range inhibited both L- and N-type VSCC in dbcAMP-differentiated NG 108-15 cells whereas nifedipine mainly inhibited L-type calcium channels.